Real Time Monitoring System Eggtray Production Process PT.Sinar Era Box Gresik - Muhammad Rosyid Kurniawan; Rifki Fahrial Zainal; R Dimas Adityo (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
PT. Sinar Era Box Gresik does not yet have a production process information system, so that all activities of production process process have not been well accommodated, for example production data file such as raw material mixing data, HPP (Cost of Production), production cost, raw material stock, production stock. Coordinator in data entry all aspects also not terakomodir well, and also data entry is still done manually and still have to meet with aspect concerned. System design is done by modeling language DFD (Data Flow Diagram) with system testing apply black-box testing with functional testing and error handling testing. While the programming language that is in use is PHP with framework CI (Codeigniter) and using database MySQL and the final result of the design is generating. RealTime Monitoring System Production Process Eggtray PT. Sinar Era Box Gresik is very helpful because it simplifies the employees and also the owner in monitoring the production process.